2019
DOI: 10.1103/physrevb.99.140402
|View full text |Cite
|
Sign up to set email alerts
|

Spin reorientation of the Fe moments in Eu0.5Ca0.5Fe2As2 : Evidence for strong interplay of Eu and Fe magnetism

Abstract: Using complementary polarized and unpolarized single-crystal neutron diffraction, we have investigated the temperature-dependent magnetic structures of Eu0.5Ca0.5Fe2As2. Upon 50 % dilution of the Eu sites with isovalent Ca 2+ , the Eu sublattice is found to be still long-range ordered below TEu = 10 K, in the A-typed antiferromagnetic (AFM) structure. The moment size of Eu 2+ spins is estimated to be as large as 6.74(4) µB at 2.5 K. The Fe sublattice undergoes a spin-density-wave transition at TSDW = 192(2) K … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(69 reference statements)
1
6
1
Order By: Relevance
“…In the EuFe 2 (As 1−x P x ) 2 compound, it was found that with increasing P substitution, the magnetic moments of the Eu 2+ ions cant out of the ab plane, yielding a net ferromagnetic component along the c direction. Moreover, a possible interplay between Eu and Fe magnetic sublattices should be considered, since the spin reorientation of Fe below the AFM ordering temperature of Eu was recently found in Eu 0.5 Ca 0.5 Fe 2 As 2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the EuFe 2 (As 1−x P x ) 2 compound, it was found that with increasing P substitution, the magnetic moments of the Eu 2+ ions cant out of the ab plane, yielding a net ferromagnetic component along the c direction. Moreover, a possible interplay between Eu and Fe magnetic sublattices should be considered, since the spin reorientation of Fe below the AFM ordering temperature of Eu was recently found in Eu 0.5 Ca 0.5 Fe 2 As 2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…This thus suggests that the coupling of Eu and Mn magnetism strongly depends on the magnetic structure of the Eu sublattice in this system. Given that the magnetic structure of the Eu sublattice can be tuned by an applied field, this may bring new possibilities to continuously tune the interaction between rare-earth-metal and transition-metal magnetic ions by an external magnetic field instead of chemical doping [73,74]. It is also worthwhile to study the Eu-Mn coupling in the future with various field directions.…”
Section: Discussionmentioning
confidence: 99%
“…This thus suggests that the coupling of Eu and Mn magnetism strongly depends on the magnetic structure of the Eu sublattice in this system. Given that, the magnetic structure of the Eu sublattice can be tuned by an applied field, this may bring new possibilities to continuously tune the interaction between rare-earth and transition metal magnetic ions by an external magnetic field instead of chemical doping [50,51]. So it is also worth to study the Eu-Mn coupling in the future with various field directions.…”
Section: Discussionmentioning
confidence: 99%